1986
DOI: 10.1017/s0003356100017748
|View full text |Cite
|
Sign up to set email alerts
|

The response of store lambs to protein supplementation of a roughage-based diet

Abstract: 1986). The response of store lambs to protein supplementation of a roughagebased diet. ABSTRACTThe response of 35-kg store lambs to diets containing increasing rumen-undegradable nitrogen (UDN) concentrations was measured by live-weight gain and nitrogen (N) balance. A range of UDN concentrations from 2-4 to 7-2 g/kg dietary dry matter was achieved by supplementing a basal diet of NaOH-treated barley straw, tapioca, extracted rapeseed meal and minerals with both formaldehydetreated rapeseed meal and fish meal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, the general conclusion from these and other studies (e.g. Hassan and Bryant, 1986), is that values for the requirements of lambs for UDP quoted by ARC (1980) are too low, at least in some_circumstances. Clearly, where silage is the basal diet, supplementation with a protein source of low degradability in the rumen has marked performance benefits, particularly after a period of maintenance feeding.…”
Section: Tablementioning
confidence: 64%
See 2 more Smart Citations
“…However, the general conclusion from these and other studies (e.g. Hassan and Bryant, 1986), is that values for the requirements of lambs for UDP quoted by ARC (1980) are too low, at least in some_circumstances. Clearly, where silage is the basal diet, supplementation with a protein source of low degradability in the rumen has marked performance benefits, particularly after a period of maintenance feeding.…”
Section: Tablementioning
confidence: 64%
“…However, Yilala and Bryant (1985) summarized data from several experiments and showed a clear effect of protein supplementation of silage (either fish meal or rapeseed meal) on DLWG compared with the predicted responses of lambs (Figure 1). They were unable to confirm whether this was as a result of increased microbial protein yield or the direct supply of amino acids, but subsequent studies (Hassan and Bryant, 1986) have confirmed the response to UDN.…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation
“…These findings apply when the basal diet consisted of NaOH-treated straw (Hovell, 0rskov, Grubb and MacLeod, 1983;Hassan and Bryant, 1986), grass silage (Yilala and Bryant, 1985;Povey, Webster and Weekes, 1990) or maize silage (Kossaibati and Bryant, 1990). These findings apply when the basal diet consisted of NaOH-treated straw (Hovell, 0rskov, Grubb and MacLeod, 1983;Hassan and Bryant, 1986), grass silage (Yilala and Bryant, 1985;Povey, Webster and Weekes, 1990) or maize silage (Kossaibati and Bryant, 1990).…”
Section: Introductionmentioning
confidence: 89%
“…Dietary supplements of fish meal have frequently been shown to increase live-weight gain and nitrogen (N) balance as well as to reduce food conversion ratio in store lambs given roughagebased diets (Yilala and Bryant, 1985;Hassan and Bryant, 1986). Hovell and 0rskov (1989) have proposed that the potential for growth in lambs cannot be met by diets formulated to satisfy only the needs of the rumen microflora for N and that a dietary allowance of rumen undegradable protein (UDN) is required if the potential for lean tissue growth is to be achieved.…”
Section: Introductionmentioning
confidence: 99%